Sistem Pendukung Keputusan Pemilihan Vitamin-C di Masa Pandemi Covid-19 Menggunakan Metode Weighted Product (WP) - Siti Ernawati; Wardah Ramadhanty (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2021)
Vitamin-C is a kind of water-soluble vitamins and can improve the body's resistance to disease. Vitamin-C can be found in various types of food such as vegetables and fruit. However, the body requires additional intake of vitamin-c aside from the food, that is a vitamin supplement as a complement to the nutritional needs of the body. In the pandemic Covid-19 is often associated with nutrition in the form of Vitamin-C to enhance the body's immune also to help protect body cells against free radicals, including some kind of virus. The number of forms and brands of Vitamin-C makes the community are often confused choosing a product Vitamin-C where to be consumed. To provide convenience to the public in choosing the product Vitamin-C, there is a solution to overcome these problems is the existence of a decision-making system for selecting products Vitamin-C using the Method of Weighted Products (WP). The method of Weighted Product method is a method of the determination in a decision by way of multiplication to be able to connect the value of the attribute. The results of the calculations in the study is ranking the highest value that can be recommended as the primary choice for people to choose products vitamin-c to be consumed in the pandemic covid-19. From the results of the calculation can be specified Brand of Vitamin-C You C 1000 to get the value of the highest 0,0253. Because You C 1000 vitamin supplements in liquid form that is easily taken, there are also Vitamin-C 1000 milligrams that can be consumed every day.